Social learning in karawitan education: contemporary patterns of cultural transmission in elementary schools of Surakarta - Karsono Karsono; Khusnul Mutiara Wardani; Joko Daryanto; Endrise Septina Rawanoko; Deni Zein Tarsidi; Moh. Salimi; Brian Rusty Santosa (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This study explores contemporary patterns of cultural transmission of gamelan among children in Surakarta through the interconnection between formal school learning and community-based learning. Using an ethnopedagogical perspective grounded in Social Learning Theory (Bandura, 1986), the research examines how observation, imitation, modeling, and reinforcement function as interconnected processes in karawitan education. Data were collected through an ethnographic approach that included interviews, observations, and visual documentation by observing extracurricular practices and gamelan learning activities in elementary school programs in Surakarta. The findings show that gamelan learning functions not only as musical instruction but also as a moral enculturation process, where collective practices cultivate social values such as rukun (harmony), gotong royong (cooperation), and tata krama (cultural respect). These findings affirm that the sustainability of Javanese musical heritage depends on active collaboration between schools and local communities, which transforms traditional music into a living pedagogical medium. Integrating traditional arts into formal education can foster mindful, meaningful, and joyful learning, a culturally grounded approach that blends skills, empathy, and collective happiness.